If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + -16 = 2w Reorder the terms: -16 + 6w = 2w Solving -16 + 6w = 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -16 + 6w + -2w = 2w + -2w Combine like terms: 6w + -2w = 4w -16 + 4w = 2w + -2w Combine like terms: 2w + -2w = 0 -16 + 4w = 0 Add '16' to each side of the equation. -16 + 16 + 4w = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 4w = 0 + 16 4w = 0 + 16 Combine like terms: 0 + 16 = 16 4w = 16 Divide each side by '4'. w = 4 Simplifying w = 4
| 3/4x-16=8 | | 12/34=n/96 | | 8c-19=6c+5 | | x+3.8=8.6 | | 17=-7p+38 | | 17s-20=13s | | 3m-11=22 | | 7y-10=5y+6 | | -8(x-1)=-9x | | 8(7b-5)= | | 3x+4=43 | | 3y+3=6y-4y | | x+6+2x-3= | | 2/5(5-a)=2 | | R+5.3=0.4 | | -5d=155 | | -3/4+5/8 | | -18+y=93 | | 6(1+c)=5(c-5) | | 7.5=2x-1.5 | | 1+4x=5-6x | | 3x+38=8x+5 | | 2/5+1/3-13/15 | | 8x^2=-4x-5 | | 0.1x+0.05y+5y=100 | | 6x-5/3x | | 3x-2x-8=0 | | -1/5-7/10 | | 5n+7=57 | | -9m-(4+3m)=-(2m-1)-5 | | -x^2+11x+80=0 | | s/8=2 |